1995
DOI: 10.1128/aac.39.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic and anaerobic environments on antistaphylococcal activities of five fluoroquinolones

Abstract: A previously established in vitro pharmacodynamic system was used to evaluate the antistaphylococcal activities of five fluoroquinolones under both aerobic and anaerobic conditions. Staphylococcus aureus ATCC 29213 was exposed to a 5-g/ml concentration of each of the following fluoroquinolones: ciprofloxacin, ofloxacin, temafloxacin, sparfloxacin, and clinafloxacin. Terminal elimination half-lives of 4, 6, 8, 8, and 13 h were simulated for the respective drugs. Each fluoroquinolone was bactericidal under both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The lack of antibiotic activity we observed in anaerobic sediment microcosms is consistent with reports of delayed, diminished, or lack of antibiotic activity against infections involving anaerobic bacteria (Lewin et al, 1991;Zabinski et al, 1995;Morrissey and George, 2001;Stein and Goldstein, 2006). All these studies have been performed on clinical isolates and pure cultures, but there is no reason to expect that soil microbes would behave differently.…”
Section: Discussionsupporting
confidence: 76%
“…The lack of antibiotic activity we observed in anaerobic sediment microcosms is consistent with reports of delayed, diminished, or lack of antibiotic activity against infections involving anaerobic bacteria (Lewin et al, 1991;Zabinski et al, 1995;Morrissey and George, 2001;Stein and Goldstein, 2006). All these studies have been performed on clinical isolates and pure cultures, but there is no reason to expect that soil microbes would behave differently.…”
Section: Discussionsupporting
confidence: 76%
“…Partition coefficients of ofloxacin and sparfloxacin, expressed as the ratio of quinolone concentration in n-octanol and 0.1 M phosphate buffer (pH 7.0) at 25°C, were 0.34 and 0.79, respectively. 18 This result means that ofloxacin is twofold more hydrophilic than sparfloxacin and therefore its uptake may partially occur through a different mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Diffusion of solutes across the intestinal epithelium depends on their lipophilicity. Sparfloxacin is one of the most hydrophobic fluoroquinolones 18 and may thus more readily cross the enterocyte membrane leaflets than other fluoroquinolones. This diffusion may be promoted by the binding of this particular fluoroquinolone to as yet unknown intracellular components, resulting in a reduction of the intracellular concentration of free sparfloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Wise et al found sparfloxacin and ciprofloxacin were bactericidal against E. coli under anaerobic conditions (1). Our group found five older fluoroquinolones to be bactericidal against staphylococci, regardless of whether studied in an aerobic or anaerobic environment, although the rate of kill appeared slower anaerobically (11).…”
mentioning
confidence: 99%